Determinants of Job Satisfaction and Its Implications for the Lecturers Performance - Subarto Subarto; Dede Solihin; Derita Qurbani (Faculty of Economics, State University of Jakarta., 2021)
The purpose of this research is to examine the positive effects of leadership style, work environment, and organizational climate on lecturer performance through Pamulang University’s job satisfaction. Researchers used the quantitative research method in this study. The data was collected by using questionnaires distributed through surveys. Proportional random sampling was used, earning 135 samples, and partial least squares (PLS) were used for statistical analysis. The results show that leadership style, work environment, and organizational climate have an impact on job satisfaction. Job satisfaction affects the performance of lecturers. Leadership style, work environment, and organizational atmosphere will also affect the performance of lecturers. Job satisfaction can mediate the influence of leadership style, work environment, and organizational climate on lecturer performance. This research is expected to be a recommendation for Pamulang University on how to improve lecturer performance which can be tried by improving leadership style, work environment, organizational climate, and job satisfaction.